PENGARUH BUDAYA ORGANISASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PT. KERETA API INDONESIA (PERSERO) (STUDI KASUS PADA UNIT SARANA PT. KERETA API INDONESIA (PERSERO) DIVISI REGIONAL II SUMATERA BARAT) - Jasmalinda Jasmalinda (Sekolah Tinggi Pariwisata Mataram, 2021)
This study aims to analyze: 1) the influence of organizational culture on employee performance. 2) the influence of work discipline on employee performance. 3) the influence of organizational culture and work discipline on employee performance. The population of this research is all employees or employees at PT. Kereta Api Indonesia (Persero) Regional Division II West Sumatra. The sample amounted to 93 people with the sampling technique in the form of a total sampling technique. The data analysis technique used is descriptive analysis and multiple linear regression analysis.The results of the study indicate that: (1) organizational culture has a significant positive effect on employee performance in the Facility unit of PT. Kereta Api Indonesia (Persero) Regional Division II West Sumatra. Where a coefficient of 0.464 with a significant value of 0.001 <0.05 means that Ha is accepted and Ho is rejected, (2) work discipline has a significant positive effect on employee performance at the Facility unit of PT. Kereta Api Indonesia (Persero) Regional Division II West Sumatra. Where the coefficient value is 0.973 with a significant value of 0,000 < 0.05 means that Ha is accepted and Ho is rejected. (3) organizational culture and work discipline significantly influence jointly on employee performance in the Facility unit of PT. Kereta Api Indonesia (Persero) Regional Division II West Sumatra. Where obtained Fhitung value of 324,411 with a significant value of 0,000 <0,05 means that Ha is accepted and Ho is rejected. The result of R2 is 0.878. This can be interpreted that organizational culture and work discipline are factors that influence the performance of employees with a percentage of 87.8%, the remaining 12.2% is influenced by other variables not examined in this study.